PENGEMBANGAN METODOLOGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM: KARAKTERISTIK, PRINSIP DAN DIMENSINYA - Djuwairiyah Djuwairiyah; Irsyadul Ibad (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2022)
Teacher has existencial strategic in delivering student to reach learning success. Learning success is not reached easily without there is an excellent planning by the teacher. Learning method is not the only one of learning success determinant indeed, but the excellent teaching-learning process of Islamic religion education will not be successful without the right methodology. Because of that this article tried to give description about the urgency of Islamic religious education learning methodology development, principle and basis in developing Islamic religion education learning methodology, as well as the Islamic religion education characteristic.